A Scalable and Participatory Sustainable Rangeland Management toolkit with a holistic and multidisciplinary approach to rehabilitate degraded rangelands - Louhaichi, Mounir; Gamoun, Mouldi; Hassan, Sawsan (Kenya Agricultural and Livestock Research Organization, 2022)
Rangelands contribute significantly toward improving livelihoods, offering food security, trade, and tourism for pastoral communities. Numerous challenges include poor government policies, loss of indigenous knowledge, and top-down approaches toward sustainable rangeland rehabilitation that often fail to consider local development adoption and sustainability. In such situations, effective management is needed for sustainable rangeland ecosystem goods and services in a context characterized by rainfall unreliability, poor soil nutrient status, and high uncontrolled grazing. This paper presents a new comprehensive toolkit for identifying and combining suitable and site-specific interventions aimed at reversing the trend of degraded arid rangelands. This toolbox is founded on science-based evidence and experienced practitioners. For severely degraded arid rangelands, the preference of applying an isolated technology may be insufficient to halt degradation. Through targeting a landscape scale that uses an integrated and multidisciplinary approach, this promising tool/approach aims to address the biophysical and socioeconomic linkages and trade-offs existing between the different land uses. The approach highlights the important role of rangeland governance. It also underscores the need to base decision-making on both indigenous knowledge and modern science, in order to empower communities to make good choices based on the best information available.